(untitled) (Letras, 2019)
This article presents an analysis of the deceitful discourse used by Trotaconventos to try to convince her listeners to accept the Archpriest’s amorous requests. As we will see here, the point of departure of this discourse is the characterization the go-between makes of herself in moral terms. She achieves this successful self-portrait using a series of images and exempla whose meanings and connotations she modifies at will, to best serve her deceitful goals. To support my argument I will use some concepts taken from a set of recent discoveries made in the field of the neurosciences that point towards a more accurate and scientific description of the origins and nature of our own human race, and the way these have given shape to our moral ideas. Those concepts will help me explain the reasons why, despite all the Book’s warnings and admonishments, whoever gets exposed to its “fablares fermosos” (beautiful talk) and that of its characters cannot avoid running a high risk of falling prey of their traps.